154k views
1 vote
9x^2+6x+3=0
Find solution in brackets

2 Answers

5 votes

Answer:

Explanation:

Use PEMDAS

First, exponents.

81x+6x+3

Now, add.

87x+3=0

Subtract on both sides.

87x=-3

Divide 3 by 87 to isolate x.

-0.03448275862

Hope this helps!

User Nathan Kovner
by
4.6k points
3 votes

Answer:

x = { (-1+√2i)/3 and (-1 -√2i)/3)}

Explanation:

The given equation is a quadratic equation.

9x^2 + 6x + 3 = 0

Here 3 is the common factor.

3(3x^2 + 2x + 1) = 0

Dividing both sides by 3, we get

3x^2 + 2x + 1 = 0

Here the value of a = 3, b = 2 and c = 1 by comparing the given equation with the general form of quadratic equation y = ax^2 + bx + x

We have quadratic formula to find the solution.

x = (-b ± √(b^2 - 4ac))/ 2a

Now we have to plug in a = 3, b = 2 and c =1 in the above formula, we get

x = (-2 ± √(2^2 - 4*3*1)) / 2*3

x = (-2±√-8) /6

√-8 = √-1√4√2 = 2√2i [√-1 = i]

Therefore, x = (-2±2√2i) / 6

Here the roots are complex.

we can take out 2 in the numerator because it is a common factor.

x = 2(-1 ±√2i)/6

Simplifying the above, we get

x = (-1 ±√2i)/3

There are two roots

x = { (-1+√2i)/3 and (-1 -√2i)/3)}

Hope you will understand the concept.

Thank you.

User Falkb
by
4.6k points